2012
DOI: 10.1021/cm303259j
|View full text |Cite
|
Sign up to set email alerts
|

Why Substitution Enhances the Reactivity of LiFePO4

Abstract: The impact of substitution at the Fe site in LiFePO 4 on reaction pathway, kinetics, and crystallographic changes upon electrochemical delithiation has been determined. Substitution was found by X-ray diffraction to reduce the lattice mismatch between the Li-rich and the Li-poor phases of the substituted samples as compared to the unsubstituted one. Substitution was also found, by monitoring the 200 reflection peaks of both the triphylite and heterosite phases, to increase the composition width of the single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 23 publications
(32 reference statements)
7
50
0
1
Order By: Relevance
“…Through cationic substitution, the lattice mismatch can be reduced, accompanied by an increased Li solubility range. Omenya et al reported that vanadium substitution on the iron site in LiFePO 4 increases the rate of Li removal and insertion [43,44]. As shown in Fig.…”
Section: Strain Accommodationmentioning
confidence: 93%
See 1 more Smart Citation
“…Through cationic substitution, the lattice mismatch can be reduced, accompanied by an increased Li solubility range. Omenya et al reported that vanadium substitution on the iron site in LiFePO 4 increases the rate of Li removal and insertion [43,44]. As shown in Fig.…”
Section: Strain Accommodationmentioning
confidence: 93%
“…(c) Diffraction patterns of Li 0.5 FePO 4 (black) and Li 0.5 Fe 0.85 V 0.1 PO 4 (red), insert shows magnified (2 0 0) diffraction peaks of triphylite and heterosite phases. Reproduced from[44] with permission from the American Chemical Society.…”
mentioning
confidence: 99%
“…For instance, the nucleation barrier in a phase-separating material was shown to be inversely proportional to the surface area to volume ratio of the nanoparticles 34 . Additionally, Nb doping 46 and V substitution 47 in LFP reduce the lattice mismatch and increase the solubility limits, both strong indicators of decreased transformation barrier. Mn substitution in LiFePO 4 , on the other hand, has been shown to eliminate the nucleation barrier and result in extensive solid solubility upon lithiation 48 .…”
mentioning
confidence: 99%
“…The magnetic properties are widely used to determine magnetic interactions, sample purity, transition metal oxidation states, and structural ordering [29,35,36,41]. The magnetic susceptibility, χ, of Li 2 Fe 1-3x/2 V x P 2 O 7 (x = 0, 0.025, 0.05) from 2 to 300 K is shown in Figure 4(a).…”
Section: Resultsmentioning
confidence: 99%